Impairment for Medication Management in Older Adults: Validity of a Family Report Measure. Issue 3 (3rd May 2020) - Schmidt, Nicholas E.; Steffen, Ann; Meuser, Thomas M.
ABSTRACT: Objectives : Medication nonadherence can have significant consequences for the health of older adults. Difficulty managing medications is often a sign of cognitive impairment, and monitoring is an early caregiving task for family members. This study examined a screening tool for independence in medication management. Methods : Reliability and validity of the screening tool were assessed in a sample of 152 female care partners for a relative aged 65+years. Results : The tool showed sound test-retest reliability, convergent and discriminant validity, and test utility, such that medication assistance was not better predicted by a global rating of cognitive impairment. Conclusions : In context of cognitive impairment, detection of medication mismanagement could be improved in both primary care and specialty health encounters through adoption of this single-item screening tool. Clinical Implications : This single-item report can be used to quickly facilitate discussions of medication management and cognitive impairment screening in office visits. The item also shows promise for efficient measurement of impairment in medication management than typical IADL assessment language.